1996
DOI: 10.1007/bf02348332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Snow Cover on the Distribution of Non-migratory Sika Deer on the Top of Mt. Tanzawa, Japan

Abstract: On the basis of 268 direct sika deer observations and 212 radio locations of three individuals, the influence of snow on deer distribution was studied. During the period of snow absence or its shallow cover, the deer did not show any preferences towards slope aspect. However, when the snow coverage became deeper, the deer used westerly exposures (having shallower snow cover) more intensively. Later on, when the snow started to melt on the easterly slope aspects deer mostly used those exposures due to relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In March 1995 a combination of high population density and deep snow led to a high mortality rate among deer, with the result that direct observations stopped because individuals were seen only sporadically. In 1994, although snow covered the study area from mid-January onwards, it was too shallow in January to affect food availability and the consequent deer space use pattern; however, this did occur in February 1994 (Borkowski et al 1996). In 1995, both January and February were snowless.…”
Section: Study Areamentioning
confidence: 93%
“…In March 1995 a combination of high population density and deep snow led to a high mortality rate among deer, with the result that direct observations stopped because individuals were seen only sporadically. In 1994, although snow covered the study area from mid-January onwards, it was too shallow in January to affect food availability and the consequent deer space use pattern; however, this did occur in February 1994 (Borkowski et al 1996). In 1995, both January and February were snowless.…”
Section: Study Areamentioning
confidence: 93%
“…Although in 1994, snow depth in the study area rarely exceeded 50 cm, it contributed to the deer slope use in winter (Borkowski, Habuto & Furubayashi, 1996).…”
Section: Study Areamentioning
confidence: 98%
“…From these data, we calculated the percentage of each landscape characteristic in each mesh by using Quantum GIS (Version 1.6.0, http://qgis.osgeo.org/, accessed 2 Aug 2012). Previous studies have found that deer species avoid areas of deep snow (Borkowski et al 1996, Kiffner et al 2008, Honda 2009) because the snow interferes with their movement (Takatsuki 1992) and covers their food (Robinson and Merrill 2011). However, Kaji et al (2010) pointed out the importance of evergreen forest, where the snow is less deep than in other habitats because some of it is caught by the evergreen canopy.…”
Section: Data Sourcesmentioning
confidence: 99%